Passively Q-switched erbium-doped fiber laser at C-band region based on WS_2 saturable absorber - Ahmad, Harith; Ruslan, N.E.; Ismail, M.A.; Reduan, S.A.; Lee, C.S.J.; Sathiyan, S.; Sivabalan, S.; Harun, Sulaiman Wadi (Optical Society of America, 2016)
We demonstrate a Q-switched erbium-doped fiber laser using tungsten disulfide (WS2) as a saturable absorber. The WS2 is deposited onto fiber ferrules using a drop-casting method. Passive Q-switched pulses operating in the C-band region with a central wavelength of 1560.7 nm are successfully generated by a tunable pulse repetition rate ranging from 27.2 to 84.8 kHz when pump power is increased from 40 to 220 mW. At the same time, the pulse width decreases from a maximum value of 3.84 μs to a minimum value of 1.44 μs. The signal-to-noise ratio gives a stable value of 43.7 dB. The modulation depth and saturation intensity are measured to be 0.99% and 36.2 MW/cm2, respectively.